This equals 365 i know that is not what you ask but this is what i know
That doesn’t make any sense to me sorry
Answer:
The equation is 4(x-3) -(5x+1) = 3
The next step is solving the equation is to apply the distributive property and the equation becomes 4x - 12 - 5x - 5 = 3.
Hope I helped :D
Step-by-step explanation:
5.3×10^5=53×10^4
53×10^4+3.8×10^4
=56.8×10^4
=5.68×10^5. Hope it help!
If I'm interpreting this right, it's -36 since a half times ten is 5... so it comes down to 5-41 which equals -36.